Revisiting the Late Jurassic-Early Cretaceous of the NW South Iberian Basin: new ages and sedimentary environments - Campos-Soto, Sonia; Benito, M. Isabel; Mas, Ramón; Caus, Esmeralda; Cobos, Alberto; Suárez-González, Pablo; Quijada, I. Emma (Journal of Iberian Geology, 2016)
The study of the Upper Jurassic-Lower Cretaceous deposits (Higueruelas, Villar del Arzobispo and Aldea de Cortés Formations) of the South Iberian Basin (NW Valencia, Spain) reveals new stratigraphic and sedimentological data, which have significant implications on the stratigraphic framework, depositional environments and age of these units. The Higueruelas Fm was deposited in a mid-inner carbonate platform where oncolitic bars migrated by the action of storms and where oncoid production progressively decreased towards the uppermost part of the unit. The overlying Villar del Arzobispo Fm has been traditionally interpreted as an inner platform-lagoon evolving into a tidal-flat. Here it is interpreted as an inner-carbonate platform affected by storms, where oolitic shoals protected a lagoon, which had siliciclastic inputs from the continent. The Aldea de Cortés Fm has been previously interpreted as a lagoon surrounded by tidal-flats and fluvial-deltaic plains. Here it is reinterpreted as a coastal wetland where siliciclastic muddy deposits interacted with shallow fresh to marine water bodies, aeolian dunes and continental siliciclastic inputs. The contact between the Higueruelas and Villar del Arzobispo Fms, classically defined as gradual, is also interpreted here as rapid. More importantly, the contact between the Villar del Arzobispo and Aldea de Cortés Fms, previously considered as unconformable, is here interpreted as gradual. The presence of Alveosepta in the Villar del Arzobispo Fm suggests that at least part of this unit is Kimmeridgian, unlike the previously assigned Late Tithonian-Middle Berriasian age. Consequently, the underlying Higueruelas Fm, previously considered Tithonian, should not be younger than Kimmeridgian. Accordingly, sedimentation of the Aldea de Cortés Fm, previously considered Valangian-Hauterivian, probably started during the Tithonian and it may be considered part of the regressive trend of the Late Jurassic-Early Cretaceous cycle. This is consistent with the dinosaur faunas, typically Jurassic, described in the Villar del Arzobispo and Aldea de Cortés Fms.